Tannin-based hard carbons as high-performance anode materials for sodium-ion batteries. (March 2022) - Tonnoir, H.; Huo, D.; Canevesi, R.L.S.; Fierro, V.; Celzard, A.; Janot, R.
Abstract: The demand for efficient and cheap electrochemical storage devices is very high today. Na-ion batteries are emerging as a promising alternative to Li-ion batteries for large-scale applications because of the much larger abundance of sodium. Among the different negative electrode materials allowing Na insertion at low potentials, hard carbons are the materials with the best electrochemical performances reported so far. Here we investigate the synthesis of hard carbons from tannins, an abundant and cheap bio-sourced carbon precursor made of polyphenolic molecules. We show that by a well-controlled synthesis method and high-temperature pyrolysis (1600°C), a hard carbon with developed ultra-microporosity is obtained. This hard carbon delivers a reversible capacity of 306 mAh g −1 at C/20 with a first-cycle coulombic efficiency of 87%. To our knowledge, these electrochemical performances are among the best ever reported in the literature for biomass-derived hard carbons. Graphical abstract: Image 1